2018
DOI: 10.1016/j.conctc.2018.03.007
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the effectiveness and reliability of the Vibrant Soundbridge and Bonebridge auditory implants in clinical practice: Study design and methods for a multi-centre longitudinal observational study

Abstract: BackgroundThe Vibrant Soundbridge middle ear implant and the Bonebridge bone conducting hearing device are hearing implants that use radio frequency transmission to send information from the sound processor to the internal transducer. This reduces the risk of skin problems and infection but requires a more involved surgical procedure than competitor skin penetrating devices. It is not known whether more complex surgery will lead to additional complications. There is little information available on the reliabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It is less widely used but has previously been used in a number of studies for examining VSB and BB satisfaction. [1][2][3][4][5][6][7][8] Patient responses may be "very satisfied," "satisfied," "sometimes satisfied/ dissatisfied," "dissatisfied," "very dissatisfied," or "does not apply." The HDSS questionnaire has not been validated, but its questions are particularly suited to implants such as those under investigation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is less widely used but has previously been used in a number of studies for examining VSB and BB satisfaction. [1][2][3][4][5][6][7][8] Patient responses may be "very satisfied," "satisfied," "sometimes satisfied/ dissatisfied," "dissatisfied," "very dissatisfied," or "does not apply." The HDSS questionnaire has not been validated, but its questions are particularly suited to implants such as those under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…It is less widely used but has previously been used in a number of studies for examining VSB and BB satisfaction. 1 - 8 Patient responses may be “very satisfied,” “satisfied,” “sometimes satisfied/dissatisfied,” “dissatisfied,” “very dissatisfied,” or “does not apply.” The HDSS questionnaire has not been validated, but its questions are particularly suited to implants such as those under investigation. The authors were unable to retrieve any instructions on questionnaire administration or analysis in the published articles identified above.…”
Section: Methodsmentioning
confidence: 99%
“…The fixation of the transducer can cause poor esthetics. Surgical procedures, such as implanting bone-anchored hearing aids (BAHAs), are additional options [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ] but involve various risks, such as adverse medical and surgical events, infection, and follow-up surgery [ 32 , 33 ]. Some patients also refuse BAHA implantation because of cosmetic considerations [ 34 ].…”
Section: CC Applicationsmentioning
confidence: 99%
“…The focus groups were comprised of surgical and audiological representatives from the contributing clinical sites. The full study design and development of this research protocol were reported by Vickers et al [6].…”
Section: Methodsmentioning
confidence: 99%